2009
DOI: 10.1037/a0014063
|View full text |Cite
|
Sign up to set email alerts
|

Sports participation and juvenile delinquency: The role of the peer context among adolescent boys and girls with varied histories of problem behavior.

Abstract: In a study of 1,344 urban adolescents, the authors examined the relation between participation in organized sports and juvenile delinquency. They compared youth who participated in sports to those who only participated in nonathletic activities and to those who did not participate in any organized activities. They also examined the indirect relations between sports and delinquency via 2 peer-related constructs-deviant peer affiliations and unstructured socializing. Finally, they examined the extent to which ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 79 publications
0
40
0
4
Order By: Relevance
“…In another study of sports participation, the researchers found that the conclusions about the riskiness of participation in sports differed by referent group. That is, the odds of nonviolent delinquency were higher among boys who participated in sports compared to boys who participated only in nonathletic activities, but not when compared to boys who did not participate in any organized activity (Gardner, Roth, & Brooks-Gunn, 2009). …”
Section: Programs As a Context Of Developmentmentioning
confidence: 99%
“…In another study of sports participation, the researchers found that the conclusions about the riskiness of participation in sports differed by referent group. That is, the odds of nonviolent delinquency were higher among boys who participated in sports compared to boys who participated only in nonathletic activities, but not when compared to boys who did not participate in any organized activity (Gardner, Roth, & Brooks-Gunn, 2009). …”
Section: Programs As a Context Of Developmentmentioning
confidence: 99%
“…However, studies PARTICIPATION, SOCIAL SKILLS, AND CONDUCT PROBLEMS 22 in adolescence suggest that friends' characteristics, such as their level of prosociality or deviancy, are likely to mediate the association between activity participation and adolescent adjustment (Fredricks & Eccles, 2005;Gardner, Roth, & Brooks-Gunn, 2009;Simpkins, Eccles, & Becnel, 2008). At a more micro-level, one of the underlying processes might involve the quality of friends' social skills.…”
Section: The Mediation Model Of the Association Between Activity Partmentioning
confidence: 99%
“…As it has been previously pointed out, sports-related activities overwhelm and have also been more studied. A higher degree of well-being in students that practice sports has been observed by Dimech and Seiler (2011), alongside with some interesting benefits, like preventing delinquence (Gardner, Roth & Brooks-Gunn, 2011), having higher school marks (Cladellas et al, 2013;Cladellas et al, 2015) or having more opportunities for social interaction (Schafaer, Simpkins, Svest & Price, 2011), citing just some recent contributions.…”
Section: Physical and Sports Activitiesmentioning
confidence: 86%